A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China - Li, Kaiqin; Liang, Hongbin (Zootaxa, 2018)
A total of 28 Zeugophorinae taxa are recognized in China. Two new species of the subgenus Pedrillia are described from China: Zeugophora (Pedrillia) emeica Li & Liang, sp. nov. and Zeugophora (Pedrillia) nigroapica Li & Liang, sp. nov. Three species are recorded for the first time in China: Zeugophora (Pedrillia) longicornis Westwood, 1864; Zeugophora (Pedrillia) bicoloriventris Pic, 1911; and Zeugophora (Pedrillia) indica Jacoby, 1903. For Zeugophora (Pedrillia) longicornis Westwood, 1864 = Zeugophora (Pedrillia) bicoloriventris Pic, 1911, a new junior synonym is proposed. Keys to the Chinese species of the subgenera Zeugophora and Pedrillia and a check list of the species are provided.